Effective magnetic moment in cyclodextrin–polynitroxides: potential supramolecular vectors for magnetic resonance imaging1. Issue 93 (11th October 2015) - Caglieris, F.; Melone, L.; Canepa, F.; Lamura, G.; Castiglione, F.; Ferro, M.; Malpezzi, L.; Mele, A.; Punta, C.; Franchi, P.; Lucarini, M.; Rossi, B.; et al.
<x xml:space="preserve">Abstract</x> Hepta-TEMPO β-CD has a molecular effective magnetic moment of 4.2 μB that is responsible of a NMR relaxivity up to 1.60 mm−1 s−1, not far from the values reported for Gd-based contrast agents, thus resulting a promising candidates as non-toxic MRI contrast agents.